Exacerbation of experimental murine cutaneous leishmaniasis with CD4+ Leishmania major-specific T cell lines or clones which secrete interferon-gamma and mediate parasite-specific delayed-type hypersensitivity. - Titus,RG; Müller,I; Kimsey,P; Cerny,A; Behin,R; Zinkernagel,RM; Louis,JA (Eur J Immunol, 1991)
Leishmania major-specific T cell lines were derived from mice sensitized to the parasite. The cells were of the CD4+ T cell lineage and, upon adoptive transfer, were found to be capable of inducing parasite-specific delayed-type hypersensitivity. Adoptive transfer of these L. major-specific T cells to syngeneic recipients which were either normal, T cell deficient or B cell and antibody deficient led to exacerbation of infection upon subsequent challenge with L. major. This suggested that host T cells, B cells and antibody were not required for the L. major-specific T cells to exert their exacerbative effect on the course of cutaneous leishmaniasis. Additional studies revealed that the adoptive transfer of graded doses of these L. major-specific T cells always resulted in exacerbation of infection. Study of the localization pattern of the cells following transfer showed that they migrate preferentially to the site of the lesions. Furthermore, although the induction phase of this phenomenon was immunologically specific, its effector phase was not. Finally, T cell clones were derived from the L. major-specific T cell lines. The T cell clones were phenotypically and functionally identical to the T cell lines from which they were derived. Adoptive transfer of these parasite-specific T cell clones to normal syngeneic recipients induced an exacerbated course of infection with L. major. Interestingly, when these cloned T cells were specifically activated in vitro, the cells produced interleukin 2 and interferon-gamma, but no interleukin 4, indicating that they belong to the murine Th1 subset of CD4+ T cells.